Preventing driveline infection during left ventricular assist device support by the HeartMate 3: A survey‐based study. Issue 7 (3rd February 2022) - Saeed, Omar; Moss, Noah; Barrus, Bryan; Vidula, Himabindu; Shah, Samit; Feitell, Scott; Masser, Kristi S.; Kilic, Arman; Moin, Danyaal; Atluri, Pavan; Barati, Edo
Abstract: Purpose: Driveline infection (DLI) is a significant source of morbidity and mortality during left ventricular assist device (LVAD) support yet limited studies are available to describe the center‐level prevalence, preventive practices, and their potential effectiveness. Methods: We surveyed LVAD centers in the United States to determine program burden and preventive practices for DLI during HeartMate (HM) 3 support. An online, anonymous, question‐based survey was sent to expert providers at implanting centers. Only a single respondent completed the survey for each center. As an exploratory analysis, we compared specific DLI preventive practices between centers with low (≤10%) and high (>10%) reported prevalence of DLI. Results: Seventy‐eight centers responded to the survey (response rate: 50%). Respondents were comprised of 37 (47%) heart failure cardiologists, 27 (35%) LVAD coordinators, and 14 (18%) cardiothoracic surgeons. The prevalence of DLI during HM3 was reported as ≤10% by 27 (35%), 11%–25% by 36 (46%), and >25% by 16 (19%) centers. Thirteen (17%) centers had a body mass index threshold for device placement, 29 (37%) utilized a counter incision, 66 (81%) placed an anchor stitch, and 69 (88%) used an external device to stabilize the DL. Proportionally, more centers with a low DLI prevalence used a wound vacuum 6 (22%) versus 3 (6%, p = 0.03) than those with high DLI. Conclusion: Variation exists in reported prevalence and practices of preventing and managing driveline infections across centers during HM3 support. Further studies are warranted to develop and assess the effectiveness of standardized preventive strategies. Abstract : Reported use of preventive methods between centers with high and low prevalence of HeartMate 3 driveline infection.